CATHODIC PROTECTION OF CARBON STEEL IN 0.1N NaCl SOLUTION UNDER FLOW CONDITIONS USING ROTATING CYLINDER ELECTRODE (Journal of Engineering, 2012)
The effect of applied current on protection of carbon steel in 0.1N NaCl solution (pH=7) was investigated under flow conditions (0-0.262 m/s) for a range of temperatures (35-55°C) using rotating cylinder electrode. Various values of currents were applied to protect steel from corrosion, these were Iapp.=Icorr., Iapp.=2Icorr. and Iapp.=2.4Icorr. under stationary and flow conditions. Corrosion current was measured by weight loss method. The variation of protection potential with time and rotation velocity at various applied currents was assessed. It is found that the corrosion rate of carbon steel increases with rotation velocity andhas unstable trend with temperature. The protection current required varies with temperature and it increases considerably when the rotation velocity was increased. The protection potential decreases appreciably (shifts to more negative) with time and with increasing rotation velocity. Also it shifts to more positive with increasing temperature.